Evaluation of Corrosion Behavior and In Vitro of Strontium-Doped Calcium Phosphate Coating on Magnesium - Jung-Eun Park (MDPI AG, 2021)
This study investigated the biocompatibility of strontium-doped calcium phosphate (Sr-CaP) coatings on pure magnesium (Mg) surfaces for bone applications. Sr-CaP coated specimens were obtained by chemical immersion method on biodegradable magnesium. In this study, Sr-CaP coated magnesium was obtained by immersing pure magnesium in a solution containing Sr-CaP at 80 °C for 3 h. The corrosion resistance and biocompatibility of magnesium according to the content of Sr-CaP coated on the magnesium surface were evaluated. As a result, the corrosion resistance of Sr-CaP coated magnesium was improved compared to pure magnesium. In addition, it was confirmed that the biocompatibility of the group containing Sr was increased. Thus, the Ca-SrP coating with a reduced degradation and improved biocompatibility could be used in Mg-based orthopedic implant applications.